2020
DOI: 10.1080/15384047.2020.1824479
|View full text |Cite
|
Sign up to set email alerts
|

Expression of STAT1 is positively correlated with PD-L1 in human ovarian cancer

Abstract: Signal transducer and activator of transcription 1 (STAT1) is related to the immune microenvironment of tumorigenesis. The programmed cell death 1 (PD-1) and its ligand (PD-L1) have been reported to be important in immunotherapy by mediating tumor immune evasion. Blocking the PD-1/PD-L1 pathway can restore the endogenous anti-tumor immune response. This study aimed to examine the expression of STAT1, PD-1, and PD-L1 and the correlation between selected markers in human epithelial ovarian cancer (EOC). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Novel antitumor therapies that target the PD-1 receptor and its ligands (PD-L1) can reverse cancermediated immune evasion [40]. A set of data by Liu et al [41] suggested that STAT1 and PD-L1 are overexpressed in OC and showed a positive correlation between the two, suggesting the feasibility of targeting PD-1/PD-L1 in patients with OC. Conversely, a recent study con rmed that up-regulated STAT1 induces EOC cell proliferation, migration, and invasion; whereas its inhibition suppresses the proliferation, migration, and invasion of the EOC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Novel antitumor therapies that target the PD-1 receptor and its ligands (PD-L1) can reverse cancermediated immune evasion [40]. A set of data by Liu et al [41] suggested that STAT1 and PD-L1 are overexpressed in OC and showed a positive correlation between the two, suggesting the feasibility of targeting PD-1/PD-L1 in patients with OC. Conversely, a recent study con rmed that up-regulated STAT1 induces EOC cell proliferation, migration, and invasion; whereas its inhibition suppresses the proliferation, migration, and invasion of the EOC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription 1 (STAT1) has been demonstrated to be associated with TME. A recent study found that STAT1 expression was positively correlated with PD-L1 expression and had the potential to predict the response to ICB in patients with EOC (24). Integrins are transmembrane receptors that mediate the connection between cells and their external environment (49)(50)(51).…”
Section: Transcriptomic Signaturesmentioning
confidence: 99%
“…Signal transducer and activator of transcription 1 is overexpressed in OC compared with normal ovarian tissue ( Tian et al, 2018 ; Liu et al, 2020 ) and is associated with the overall survival of patients ( Josahkian et al, 2018 ). High levels of STAT1 evaluated by immunohistochemistry is associated with longer overall survival and progression-free survival of patients with high-grade serous ovarian cancer (HGSOC) ( Table 1 ; Koti et al, 2015 ; Au et al, 2016 ; Josahkian et al, 2018 ).…”
Section: Role Of Stat1 In Ovarian Cancermentioning
confidence: 99%
“…The blockage of IDO by iNOS-induced-NO may lead to a favorable prognosis ( Munn and Mellor, 2016 ). Our previous study suggested that the elevated PD-L1 and STAT1 may favor the checkpoint immunotherapy in patients with EOC, but may have a limit in paclitaxel-resistant patients because of the low expression of PD-L1 and STAT1 ( Liu et al, 2020 ).…”
Section: Role Of Stat1 In Ovarian Cancermentioning
confidence: 99%